Safety culture on construction sites - Abdllah Sani, Zarifah Sofia (2011)
The construction project is very unique by itself, complex and is always related to high risk working environment as compared to others. Creating a safety culture means that the employees are constantly aware of hazards including the ones that they create themselves. The aim of this research is to study safety culture on construction sites in Malaysia. To achieve this aim, elements and factors affecting the implementation of safety culture were assessed. In the present study, a survey was carried out using a detailed developed questionnaire. The questionnaire comprised the general information with a list of elements in safety culture and factors affecting the implementation of the culture on a 1-5 likert scale which was distributed to 50 safety and health officers, project managers and other project personnel. Over and above that, a few interviews with safety experts were conducted before and after the questionnaire were distributed for the purpose of validating the data extract from both literature reviews and the data collected from the survey. The data was then process using a Statistical Package for Social Sciences Version 10.0 (SPSS 10.0). The results revealed that safety policy, procedures and planning is not only the most important elements in safety culture, but also the most significant success factors in the safety culture performance. In the contrary, commitment seems to be the main barriers that need to deal with to ensure the effectiveness of safety culture implementation.